Система професійної ідентичності службовців місцевого самоврядування - Липовська, Наталія Анатолівна; Тарасенко, Тетяна Миколаївна (My University, 2020)
Модель професійної ідентичності посадових осіб місцевого самоврядування з розмежуванням принципівйого експертизи. Наукові пошуки спираються на аксіологічний підхід, що дозволилорозкрити зв'язок цінностей державної служби з факторами служби в органах місцевого самоврядуваннятіла і структуру особистості.

The ɚrticle is devoted to the definition of the content and structure of the professional identity system of the local government officials. The research is based on the institutional paradigm of considering the service in local government bodies, and the systematic approach to studying the model of the professional identity of the local government officials with a distinction of principlesof its examination. Scientific searches are relying on the axiological approach, which allowed to disclose the connection of the public service values with factors of the service in local government bodies and the personality structure.
The professional identity system оf the local government officials
Keywords: професійна ідентичність; місцеве самоврядування; професійна компентність; professional identity; professional competence; the local government official